Russia: a Euro-Pacific power? : goals, strategies and perspectives of Moscow's East Asia policy - Klein, Margarete (2014)
Zusammenfassung: Russia has been working since the mid-2000s to enhance its political, economic and military position in East Asia and establish itself as a Euro-Pacific power. Behind this development stands the wish to profit from the region's economic dynamism, modernise Russia's backward eastern regions and underline its claim to the status of a global power. Moscow can already claim successes for its East Asia policy. It has succeeded in expanding its relations with most of the East Asian nations and in joining important regional forums. Here the Kremlin is pursuing a dual strategy: expanding its “strategic partnership” with China but at the same time diversifying its relationships - rather than continuing to depend on Beijing as a “door-opener” in East Asia as it did in the 1990s. Russia has also succeeded in increasing its trade volume with East Asia, which has become its second trading region after Europe. Yet Russia's prospects of regaining its great power role in East Asia are limited. Without improving relations with Washington and Tokyo the political diversification strategy remains incomplete, while growing power asymmetry with China could see Russia edged into a junior partner role. But the greatest hindrance to Moscow's Euro-Pacific ambitions is Russia's integration into the East Asian economy almost exclusively as a raw material supplier. Faced with increasing tensions with the West, Moscow threatens to play the “East Asia card”. But a substantial eastward reorientation would tend to harm Russia's economic modernisation and the implementation of its political great power ambitions. (SWP Research Paper)